2020
DOI: 10.1016/j.celrep.2020.108278
|View full text |Cite
|
Sign up to set email alerts
|

PPARα Inhibition Overcomes Tumor-Derived Exosomal Lipid-Induced Dendritic Cell Dysfunction

Abstract: SUMMARY Dendritic cells (DCs) orchestrate the initiation, programming, and regulation of anti-tumor immune responses. Emerging evidence indicates that the tumor microenvironment (TME) induces immune dysfunctional tumor-infiltrating DCs (TIDCs), characterized with both increased intracellular lipid content and mitochondrial respiration. The underlying mechanism, however, remains largely unclear. Here, we report that fatty acid-carrying tumor-derived exosomes (TDEs) induce immune dysfunctional DCs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 50 publications
(67 reference statements)
2
101
0
Order By: Relevance
“…However, it is strongly recommended to use some intracellular organelle markers to exclude contaminations of Golgi bodies (GM130), mitochondria (Cytochrome C) or nucleus (Histone H3). In our study, GM130, Cytochrome C, and Histone H3 was excluded to make sure the purity of exosomes( Yin et al., 2020 ).
Figure 1 Isolation of exosomes from tumor culture medium (A) Illustrative overview of exosome separation.
…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it is strongly recommended to use some intracellular organelle markers to exclude contaminations of Golgi bodies (GM130), mitochondria (Cytochrome C) or nucleus (Histone H3). In our study, GM130, Cytochrome C, and Histone H3 was excluded to make sure the purity of exosomes( Yin et al., 2020 ).
Figure 1 Isolation of exosomes from tumor culture medium (A) Illustrative overview of exosome separation.
…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“…Morphologies of the purified exosomes were characterized by transmission electron microscopy (TEM; Figure 5 A), showing a mean diameter of ~40 nm, consistent with the size of previous reports ( Kalluri, 2016 ; Kalluri and LeBleu, 2020 ). Western blot analysis revealed the presence of exosome-enriched proteins (e.g., ALIX, HSP70, TSG101, CD9, and CD81)( Hessvik and Llorente, 2017 ; Huang-Doran et al., 2017 )(Data as shown in ( Yin et al., 2020 )). In our experience, we also calculated the amount of exosomes by EXOCET Exosome Quantitation Kit and found that the number of exosomes were highly correlated with the protein content by BCA ( Figure 5 B).…”
Section: Expected Outcomesmentioning
confidence: 98%
See 2 more Smart Citations
“…Tumor cells can secrete fat-containing exosomes as a fatty acid carrier and activate PPARα of DCs to induce the synthesis of lipid droplets in DCs and enhance FAO, inducing the transformation of DC metabolism from glycolysis to OXPHOS, leading to the dysfunction of DC. As a key molecule of metabolic regulation, PPARα can be used as a target of immunotherapy and has a great potential in anti-tumor therapy ( 80 ).…”
Section: Lipid Metabolismmentioning
confidence: 99%